Mucinous adenocarcinoma arising from a chronic perianal fistula: A case report and literature review - Chirukandath, Ravindran; Sharath K Krishnan; Sasi, Tinu; Sumin V Sulaiman; Adarsh K Nair; Nisthar CMT; Priyanka Mittra (Asian Journal of Medical Sciences, 2023)
Perianal fistula is a common disease affecting the general population but development of mucinous adenocarcinoma (MA) in a chronic perianal fistula is a rare entity. Due to the rare nature of the disease, there are no established guidelines regarding the diagnosis and management of the condition. The aim of this article is to report a case of MA perianal region that we managed surgically with an extra levator abdominoperineal resection and flap reconstruction.